(untitled) (Damu Journal of Sport Sciences, 2024)
Through the experience of the two researchers and their knowledge of the literature and studies. The researcher decided to delve into this topic to identify the effect of learning and thinking patterns in developing the skills of receiving the serve and sending for female students. The objectives of the research were to prepare an educational curriculum for learning the skills of receiving the serve and sending for volleyball for female students. To identify the effect of the educational curriculum in learning the skills of receiving the serve and sending for volleyball for female students. The two researchers identified the research community as second-stage female students in the College of Education for Girls, Department of Physical Education and Sports Sciences - University of Kufa for the academic year (2022-2024). Their number is (25) female students, and the steps of the field research procedures were to choose the skills used in the research. They are the front facing serve from above and receiving the serve. The research included presenting, analyzing and discussing the results. The results of the post-tests of the skills of receiving the serve and serving in volleyball for the experimental and control groups were presented and analyzed, and the results of the post-tests of the skills of receiving the serve and serving in volleyball for the experimental and control groups were presented and analyzed. The researchers concluded that the educational curriculum had a clear and effective impact in developing the skills of receiving the serve and serving for the research sample, and that the educational curriculum had a clear and effective impact in developing the skills studied. The researchers recommended the necessity of intervention and combination of theoretical and motor aspects in building educational curricula for female students of the Department of Physical Education and Sports Sciences, and the necessity of building curricula in developing other basic skills, and the necessity of applying the educational curriculum to other samples.